Top 10 research questions related to teaching games for understanding - Memmert, D.; Almond, L.; Bunker, D.; Butler, J.; Fasold, D.; Griffin, L.; Hillmann, W.; Hüttermann, S.; Klein-Soetebier, T.; König, S.; Nopp, S.; Rathschlag, M.; et al. (Research Quarterly for Exercise and Sport, 2015)
In this article, we elaborate on 10 current research questions related to the "teaching games for understanding" (TGfU) approach with the objective of both developing the model itself and fostering game understanding, tactical decision making, and game-playing ability in invasion and net/wall games: (1) How can existing scientific approaches from different disciplines be used to enhance game play for beginners and proficient players? (2) How can state-of-the-art technology be integrated to game-play evaluations of beginners and proficient players by employing corresponding assessments? (4) How can complexity thinking be utilized to shape day-to-day physical education (PE) and coaching practices? (5) How can game making/designing be helpfully utilized for emergent learning? (6) How could purposeful game design create constraints that enable tactical understanding and skill development through adaptive learning and distributed cognition? (7) How can teacher/coach development programs benefit from game-centered approaches? (8) How can TGfU-related approaches be implemented in teacher or coach education with the goal of facilitating preservice and in-service teachers/coaches` learning to teach and thereby foster their professional development from novices to experienced practitioners? (9) Can the TGfU approach be considered a helpful model across different cultures? (10) Can physical/psychomotor, cognitive, affective/social, and cultural development be fostered via TGfU approaches? The answers to these questions are critical not only for the advancement of teaching and coaching in PE and sport-based clubs, but also for an in-depth discussion on new scientific avenues and technological tools.